How effective is energy-efficient housing? Evidence from a field experiment in Mexico - Lucas W. Davis; Sebastian Martinez; Bibiana Taboada (Inter-American Development Bank (IDB), 2018)
This paper evaluates a field experiment in Mexico in which a quasi-experimental sample of new homes was provided with insulation and other energy efficient upgrades. A novel feature of our study is that we deploy large numbers of data loggers which allow us to measure temperature and humidity at high frequency inside homes. We find that the upgrades had no detectable impact on electricity use or thermal comfort, and this is true both in summer and non-summer months. These results stand in contrast to the engineering estimates that predicted up to a 26% decrease in electricity use. Part of the explanation is that air conditioner ownership is lower than expected, thus reducing the potential for reductions in energy use. In addition, we document that most households have their windows open on hot days, nullifying the thermal benefits of roof and wall insulation.
Keywords: D12; H23; Q40; Q54; 330; Energy Efficiency; Energy Demand; Thermal Comfort; Air Conditioning